Pharmacotherapeutic management of chronic viral hepatitis - Mitea, Gabriela; Radu, Marius Daniel; Ionescu, Ana Maria; Blebea, Nicoleta (Technium BioChemMed, 2021)
In infectious diseases, viral hepatitis has an increased incidence, being an important cause of morbidity and mortality, being a "sentinel" indicator of the socio-economic and hygienic-cultural standard of a geographical area. The World Health Organization (WHO) admits the following types of hepatitis viruses: A, B, B + D, C, E, F and G. Among the viral entities recognized by the WHO, a special importance in terms of incidence, evolution over time with the risk of chronicity and the therapeutic options are presented by hepatitis B and C. There is currently an effective vaccine as well as treatment for hepatitis B. There is no vaccine for hepatitis C, but in recent years considerable progress has been made in treating this disease. Also, the introduction of drugs known as direct-acting antivirals makes it possible to cure over 90% of patients within 2-3 months. But in many countries, current drug policies, regulations and prices keep treatment out of the reach of most people with hepatitis. Eradication of viral hepatitis is possible if greater emphasis is placed on prevention, diagnosis and treatment. Vaccination is very important, as it is possible for types A and B of hepatitis. Early diagnosis is also extremely important, given that there are currently very effective drugs that can prevent the development of liver cancer. The WHO also noted that about two million people worldwide become ill each year due to the reuse of syringes and stressed the importance of checking blood donors to see if they are not carriers of hepatitis B or C viruses. Therefore, the purpose of this article is to highlight the pharmacological treatment and the main therapeutic and prevention schemes currently used for patients with these liver diseases. The paper was based on the most popular methods of identification of the latest international information about the treatment of hepatitis (by electronic search using Pubmed, SciFinder, Scirus, GoogleScholar and Web of Science). We also consulted the global literature cited in the hepatitis database of the World Health Organization (WHO) updated frequent from the current literature on this topic.